2019
DOI: 10.1590/0001-3765201920180252
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric variation in pink shrimp populations at Rio de Janeiro coast (SE Brazil): are they really similar in closer areas?

Abstract: Farfantepenaeus brasiliensis and F. paulensis are the most exploited shrimps of Se-S Brazilian coast. Our aim was to verify if adjacent nursery areas with different environmental condition (Sepetiba and Guanabara bays, SE Brazil) influence on shrimp populations (eg, CPUE) and body shapes. Samplings were carried out during 12 months in those bays ca. 85 Km far from each other. Carapace length (Cl), total body length (Tl), wet weight, abdomen size and Tl/Cl ratio were used to analyze variations in shape through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
4
0
4
Order By: Relevance
“…As most organs of shrimps, including the reproductive ones, are located in the carapace, differences between sexes in the TL/CL ratio are expected, with females having a proportionally larger carapace than males as an adaptation to maximize egg production. Indeed, these differences in the TL/CL ratio are not observed when analyzing juveniles (Carvalho et al, 2019).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…As most organs of shrimps, including the reproductive ones, are located in the carapace, differences between sexes in the TL/CL ratio are expected, with females having a proportionally larger carapace than males as an adaptation to maximize egg production. Indeed, these differences in the TL/CL ratio are not observed when analyzing juveniles (Carvalho et al, 2019).…”
Section: Resultsmentioning
confidence: 92%
“…Morphometric relationships vary according to the length/age, with younger, smaller individuals having higher slopes than older, larger individuals requiring different equations for conversions (Arreguín-Sánchez, 1981;Primavera et al, 1998;Reis-Jr et al, 2019). Most of the morphometric data available for F. brasiliensis are from juveniles/subadults inhabiting coastal habitats such as estuaries and coastal lagoons (Villela et al, 1997;Branco and Verani, 1998;Pérez-Castañeda and Defeo, 2002;Albertoni et al, 2003;May-Kú et al, 2006;Freitas-Jr et al, 2011;Carvalho et al, 2019), which differ from the equations for adults such as the ones obtained here in the coast of Sergipe. Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ao comparar populações de sub-adultos de F. brasiliensis e de F. paulensis em dois sistemas estuarinos próximos no estado do Rio de Janeiro, Carvalho et al (2019) observou diferenças interespecíficas em relação ao tamanho e a morfologia dessas espécies indicando uma grande plasticidade fenotípica, apesar da ausência de variabilidade genética significativa na costa sudeste brasileira (relatada até o momento). A forma mais alongada do abdômen a partir da relação comprimento total (CT) versus comprimento da carapaça (CC) dos camarões-rosa capturados na Baía de Sepetiba em relação aos obtidos na Baía de Guanabara, sugeriu que o desenvolvimento morfológico ao longo da ontogenia desses peneídeos está intimamente relacionado às condições ambientais das áreas de berçário.…”
Section: Notas Taxonômicasunclassified

Ficha de Farfantepenaeus paulensis

Marcelo Antonio Amaro Pinheiro,
Allan Cesar Silva Scalco,
Andrea Santarosa Freire
et al. 2024
Datasets - Sistema SALVE - ICMBio
“…It has been used in a wide range of ecological studies to differentiate taxonomic groups and determine if there are multiple stocks in a population which can be beneficial to stock assessment (Asuquo & Ifon, 2019;Cronin-Fine et al, 2013;Elliott et al, 1995;Marramà & Kriwet, 2017;Schaefer, 1992). The morphometric approach has been reported to be very economical, yet highly effective in stock assessment (Carvalho et al, 2019;Ferrito et al, 2007;Hanif et al, 2019;Rios et al, 2019). Studies, including those of Schaefer (1992) and Elliott et al (1995), have shown that traditional morphometric tool is better than truss network and can be used conveniently where DNA analysis is not available.…”
Section: Introductionmentioning
confidence: 99%